2006
DOI: 10.1590/s0100-204x2006000300011
|View full text |Cite
|
Sign up to set email alerts
|

Fixação biológica de nitrogênio e fertilizantes nitrogenados no balanço de nitrogênio em soja, milho e algodão

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos da fixação biológica de nitrogênio (FBN) da cultura da soja, e a eficiência do uso de fertilizantes nitrogenados (EUFN) pelas culturas de milho e algodão, no balanço de N de um Latossolo Vermelho distroférrico, sob plantio direto, em Dourados, MS. O estudo foi feito em dois anos, concentrando-se nas safras de verão. A contribuição da FBN para a soja foi avaliada pela técnica de abundância natural de 15 N. A EUFN foi avaliada mediante a substituição dos f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 14 publications
1
19
0
15
Order By: Relevance
“…According to Broch et al (2010), soybean residues provide successive crops with N remaining from biological fixation. Even though N exportation in soybean is relatively high, the N balance in the soil is positive after growing this leguminous crop (Alves et al, 2006). The K concentration was not affected by fertilization, probably because of the initial soil K contents of 4.4 mmol c dm 3 in 2010 and 3.7 mmol c dm 3 in 2011 in the experimental area, which is considered high (Raij et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…According to Broch et al (2010), soybean residues provide successive crops with N remaining from biological fixation. Even though N exportation in soybean is relatively high, the N balance in the soil is positive after growing this leguminous crop (Alves et al, 2006). The K concentration was not affected by fertilization, probably because of the initial soil K contents of 4.4 mmol c dm 3 in 2010 and 3.7 mmol c dm 3 in 2011 in the experimental area, which is considered high (Raij et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Assuming an N content of the grain of 6.5% N, this means that this crop would accumulate 163 kg N ha -1 in the grain, or approximately 500 mg N per plant. As both the proportion of N in the grain compared to the whole shoot (the N harvest index) and the %Ndfa are both usually close to 80% (Alves et al, 2002(Alves et al, , 2003(Alves et al, , 2006, ideally soybeans used to determine 'B' value should accumulate approximately this amount of N from BNF. In the present study N derived from BNF by the soybeans inoculated with the 4 different Bradyrhizobium strains accumulated between 460 and 620 mg N per plant (910 to 1240 mg N per pot) from BNF (mean %Ndfa = 97%) very close to this value.…”
Section: Lupin (Lupinus Luteus) Lentil (Lens Culinaris) and Burr Medmentioning
confidence: 99%
“…The 'B' values for the Bradyrhizobium strains 29 W (SEMIA 5019 -B. elkanii) and CPAC 7 (SEMIA 5080 -B. japonicum), respectively, were -4.54 and -2.39 ‰ for the shoot tissue. These two strains are both recommended for inoculant manufacture in Brazil and proportional BNF inputs to soybean are generally high (Alves et al, 2003(Alves et al, , 2006. Therefore, the objective of this study was to determine the 'B' values in soybean plants grown in an open field soil inoculated with of all four recommended strains of B. elkanii and B. japonicum.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there was no significant difference in total N content of straw from the association with more or less participation of crotalaria (Table 2). Alves et al (2006) found negative balance of N or near neutrality after the cultivation of soybeans, i.e. BNF is sufficient to ensure high productivity and demand just for itself.…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, it is observed that even in the subplots without application of N, the yield obtained was high and there was no N deficiency in the leaves (Table 3), as part of N may have been from the mineralization of organic matter. However, high cotton yield with low doses of nitrogen can promote soil depletion over time, since the quantity exported by the harvest is greater than the amount added (Alves et al, 2006). According to Carvalho et al (2011), the average N exported is 33.9 kg N for each ton of cotton seed produced.…”
Section: Resultsmentioning
confidence: 99%